Evaluating Generic Structure and Language Features of Students’ Recount Texts - Sulistianti, Lilis; Fitriati, Sri Wuli; Sakhiyya , Zulfa (English Education Journal, 2024)
This study analyzes and assesses recount texts written by students, by focusing on the language features and language structures. This analysis is aimed at fostering student’s writing abilities and communication in their personal experience. The study evaluates the generic structure starting from reorientation, events, and reorientation. The language features are evaluated based on content, syntax, and vocabulary. The data of recount texts were taken from students of SMP Negeri 1 Ketanggungan Brebes, particularly class 8A which consists of 33 students, by conducting a purposive sampling technique. The generic structure of recount texts was analyzed using a scoring rubric adapted from Gerot and Wignell (1994). Meanwhile, a content-based analysis model adapted from Brown and Lee (2015) was employed to evaluate the quality of language features, especially content, syntax, and vocabulary. The quality of students’ recount texts is categorized as excellent, good, adequate, and inadequate. The result showed that 46% of students performed excellent level in orientation and 43% of students performed good level in sequence events. However, 12% of students showed an inadequate level of reorientation. It means that students have a good ability to compile the context and background of their recounts. However, some students have difficulty in concluding their recount. The quality of the language features showed that students presented the main idea and related ideas thoroughly but still needed to improve their vocabulary. The analysis results can be a reference for students to self-evaluate their writing, especially recount texts, and improve the quality. Also, it encourages teachers to apply appropriate teaching strategies in writing classrooms, which meet students’ needs.